CERPEN KERONCONG PEMBUNUHAN KARYA SENO GUMIRA AJIDARMA : ANALISIS ALUR ROBERT STANTON - , ASTRI WULANDARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The problem in the research is plot in Seno Gumira Ajidarmaâs short story entitled âKeroncong Pembunuhanâ, including plot causality, step, conflict, suspense, plausible, and sureprise ending. The selection is based on the fact that Seno Gumira is known as one of the most productive authors. âKeroncong Pembunuhanâ is chosen as research material because it is regarded importantly in postmodernism in its relation with popular culture. The results of the research are: first, plot causality